Ensuring quality in qualitative inquiry: Using key concepts as guidelines - Campbell, Debra Frances [UNESP]; Machado, Afonso A. [UNESP] (FapUNIFESP (SciELO), 2013)
The field of qualitative scientific inquiry employs a fast-growing variety of approaches, whose traditions, procedures, and structures vary, depending on the type of study design and methodology (i.e., phenomenological, ethnographic, grounded theory, case study, action research, etc.). With the interpretive approach, researchers do not utilize the same measures of validity used in positivist approaches to scientific inquiry, since there is -no one standard or accepted structure as one typically finds in quantitative research (Creswell, 2007). With the absence of a single standard, how, then, is it possible for qualitative researchers to know whether or not their study was done with rigor, that it has validity, that it is ready to submit to their peers? The research literature is sprinkled with references to quality in qualitative inquiry, which helps to construe a study's validity. Markula (2008) suggests that we validate our study's findings by assuring readers that it was done in the best possible way. While each research tradition has its own set of criteria for judging quality, we present here general concepts drawn from the literature. We hope this article will provide a framework from which qualitative researchers can judge their work before submitting it to their peerş one which will help ensure that their study was done in the best possible way..
Keywords: Qualitative methodology; Qualitative research; Validity